Cancer vaccines<subtitle>Are we there yet?</subtitle> - Michael G. Hanna, Jr (Taylor & Francis Group, 2012)
For nearly two decades there has been an abundance of research and clinical development programs underway to develop active specific immunotherapies, to educate the patient's immune response, specifically the T-cell immunity and memory, to recognize and destroy tumor cells by cell-mediated cellular toxicity. While many of these technology platforms achieved promising results in preclinical and clinical phase I and II clinical trials, essentially all but one have failed to achieve FDA market approval as a therapeutic drug product.